Postpartum dissection in bovine aorta with anomalous brachiocephalic vessels. (June 2019) - De Martino, Andrea; Falcetta, Giosuè; Scioti, Giovanni; Pucci, Angela; Bortolotti, Uberto
A 42-year-old woman, with no evidence of connective tissue disease, presented with acute aortic dissection after an uneventful vaginal delivery following an uncomplicated pregnancy. Emergency computed tomography angiography showed a bovine aortic arch with a separate origin of the left vertebral artery. At surgery, a tricuspid aortic valve was found and the aortic arch was successfully repaired with reimplantation of a button incorporating the origin of the brachiocephalic vessels. Acute aortic dissection throughout pregnancy is uncommon and favoured by hemodynamic, hormonal, and histological changes. Anomalies of the aortic arch branches might represent an increased risk of thoracic aortic diseases.